Functional and postoperative outcomes after high-intensity interval training in lung cancer patients: A systematic review and meta-analysis - Chen, Zihao; Jia, Junqiang; Gui, Dongmei; Liu, Feng; Li, Jun; Tu, Jiayuan (Frontiers in Oncology, 2023)
Objective The study evaluated the effects of high-intensity interval training (HIIT) on postoperative complications and lung function in patients with lung cancer compared to usual care. Methods We searched electronic databases in April 2022, including PubMed, Embase, the Cochrane Library, Web of Science, and the China National Knowledge Infrastructure (CNKI). Two authors independently applied the Cochrane Risk of Bias tool to assess the quality of RCTs. The postoperative complications, length of hospitalization, and cardiopulmonary functions from the studies were pooled for statistical analysis. Results A total of 12 randomized controlled trials were eligible for inclusion and were conducted in the meta-analysis. HIIT significantly increased VO2peak (MD = 2.65; 95% CI = 1.70 to 3.60; I2 = 40%; P <0.001) and FEV1 (MD = 0.12; 95% CI = 0.04 to 0.20; I2 = 51%; P = 0.003) compared with usual care. A subgroup analysis of studies that applied HIIT perioperatively showed significant improvement of HIIT on FEV1 (MD = 0.14; 95% CI = 0.08 to 0.20; I2 = 36%; P <0.0001). HIIT significantly reduced the incidence of postoperative atelectasis in lung cancer patients compared with usual care (RD = −0.16; 95% CI = −0.24 to −0.08; I2 = 24%; P <0.0001). There was no statistically significant effect of HIIT on postoperative arrhythmias (RD = −0.05; 95% CI = −0.13 to 0.03; I2 = 40%; P = 0.22), length of hospitalization (MD = −1.64; 95% CI = −3.29 to 0.01; P = 0.05), and the six-minute walk test (MD = 19.77; 95% CI = −15.25 to 54.80; P = 0.27) compared to usual care. Conclusion HIIT may enhance VO2peak and FEV1 in lung cancer patients and reduce the incidence of postoperative atelectasis. However, HIIT may not reduce the incidence of postoperative arrhythmia, shorten the length of hospitalization, or improve the exercise performance of patients with lung cancer. Systematic review registration PROSPERO, CRD42022335441